2018
DOI: 10.3389/fimmu.2018.01665
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cells Exhibit a Peculiar Phenotypic Profile in Systemic Sclerosis and Are Potent Inducers of Endothelial Microparticles Release

Abstract: The pathophysiology of systemic sclerosis (SSc) involves early endothelial and immune activation, both preceding the onset of fibrosis. We previously identified soluble fractalkine and circulating endothelial microparticles (EMPs) as biomarkers of endothelial inflammatory activation in SSc. Fractalkine plays a dual role as a membrane-bound adhesion molecule expressed in inflamed endothelial cells (ECs) and as a chemokine involved in the recruitment, transmigration, and cytotoxic activation of immune cells that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…An inhibitor of HMGB1 attenuated neutrophil activation [131] Natural killer A peculiar natural killer cell phenotype in SSc patients was identified characterized by decreased chemokine and activation receptors expression. These SSc-derived natural killer cells were potent inducers of endothelial microparticle release suggesting that there may be a role for natural killer cells in the activation of endothelial cells in SSc [133] Innate lymphoid Type 2 innate lymphoid (ILC2) cells are elevated in patients with SSc. ILC2 counts correlated with skin fibrosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An inhibitor of HMGB1 attenuated neutrophil activation [131] Natural killer A peculiar natural killer cell phenotype in SSc patients was identified characterized by decreased chemokine and activation receptors expression. These SSc-derived natural killer cells were potent inducers of endothelial microparticle release suggesting that there may be a role for natural killer cells in the activation of endothelial cells in SSc [133] Innate lymphoid Type 2 innate lymphoid (ILC2) cells are elevated in patients with SSc. ILC2 counts correlated with skin fibrosis.…”
Section: Resultsmentioning
confidence: 99%
“…This complex network of signalling between different immune cells is only now beginning to become unravelled, with new evidence emerging regularly to provide new players in SSc immunopathogenesis. For example, only a few studies have highlighted the potential for platelets , neutrophils , natural killer cells and innate lymphoid cells to be dysregulated and contribute to the pathogenesis of SSc. Type 2 innate lymphoid cells are found in higher numbers in SSc and correlate strongly with the Rodnan skin score and also the presence of lung fibrosis.…”
Section: Other Immune Cellsmentioning
confidence: 99%
“…Our results are consistent with previous reports linking NK cells to SSc 41 . In a very recent publication, Benyamine et al 42 reported a particular expression profile of NK cells in SSc and showed that this cell type induced endothelial activation 42 . These findings may provide a link between vascular damage and the immune imbalance in SSc.…”
Section: Discussionmentioning
confidence: 99%
“…MPs can originate from every type of cells, particularly under stress conditions. Endothelial cell (EC) damage is one major hallmark of SSc and lead to the shedding of endothelial MPs [EMPs; (12,13)]. Batteux et al showed in a murine model of SSc, that inhibiting MPs shedding either chemically or genetically diminishes the hallmarks of oxidative and endothelial stress but also skin and lung fibrosis (14).…”
Section: Introductionmentioning
confidence: 99%